PENGARUH MEDIA WORDWALL TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN PANCASILA KELAS IV SDN 03 SUNGAI RUMBAI - Darniyanti , Yulia; Rahayu, Rara; Ali, Gunawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of Wordwall media on student learning outcomes in Pancasila Education for fourth-grade students at SDN 03 Sungai Rumbai. The background of this research is the low student learning outcomes caused by a lack of active involvement in the learning process and the monotonous use of learning media. This research uses a quantitative approach with a Quasi-Experimental method and a Nonequivalent Control Group Design. The population and sample consisted of 38 fourth-grade students, divided into an experimental class (IV A) and a control class (IV B). The data collection instrument was a 30-item multiple-choice test that had been tested for validity and reliability. Data analysis included the Shapiro-Wilk normality test, Levene's Test for homogeneity, and the Independent Samples T-Test with the help of SPSS 25. The results showed that the average posttest score of the experimental class was 82.15, while the control class was 77.47. The hypothesis test obtained a Sig. (2-tailed) value of 0.000 < 0.05, meaning H₀ is rejected and Hₐ is accepted. It is concluded that there is a significant effect of using Wordwall media on the learning outcomes of fourth-grade students at SDN 03 Sungai Rumbai.